Changes of Placental Diameter Thickness and Cotyledon in Eclampsia - Sultana, S; Hossain, GA; Rahman, MH; Hasan, N; Sultana, SZ; Khalil, M (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):127-31 The abstract of this article is available on the PubMed website